Reconstituição das vazões naturais a jusante das pequenas centrais hidrelétricas Rio Bonito e Suíça: Rio Santa Maria da Vitória (ES) - Silva, Adriellem Lidia Marta Soares da (2014)
The knowledge of the natural streamflow of rivers is relevant to, among many other reasons, evaluate the anthropogenic impact in watersheds. Thus, it aims to create tools that contribute to an efficient management of water resources. Santa Maria da Vitória River (ES) is crucial for the socioeconomic development of the metropolitan region of Grande Vitória. Additionally, many ecosystems and agricultural communities are dependents of this river. Given that hydroelectric power generation is one of the most important uses of the Santa Maria da Vitória River, through the Small Hydroelectric Plants Rio Bonito and Suíça, this research aims to better understand the influence of these SHP`s on the natural streamflow of this river. Besides the analysis of streamflow time series and precipitation time series measured at the Santa Leopoldina gauge station, comparing the pre-dam with the post-dam period, the reconstruction of the natural daily mean streamflow and monthly mean streamflow was also carried out, using the MOVE.1 (type 1) extension method and using the streamflow time series measured at the Marechal Floriano gauge station, which is located at Jucu watershed. From the hydrometric data of Santa Leopoldina gauge station, the statistical analysis revealed a decrease of the 7, 30 and 90-day duration low flow for the post-dam period. The reconstructed 50, 90 and 95-percent duration streamflows and the reconstructed long-term monthly streamflows are smaller than the measured streamflows. Beyond of the existence of the SHP`s, changes on the land use can have influence on the results found. The streamflows measured at Santa Leopoldina gauge station, due to it`s measurement hour, may be an inaccurate way of showing the flow oscillating downstream of the SHP`s. Consequently, a continuous streamflow measurement downstream of SHP`s becomes necessary and a new reconstruction of the natural streamflow of Santa Maria da Vitória River is recommended through the water balance of the reservoirs, using the SHP`s operatives data.